The Influence of Brand Image, Perceived Value and Brand Trust on Repurchase Intention of Pinkflash Product on Shopee E-Commerce - Saharani, Yannira Elda; Zawawi, Zawawi; Mandasari, Virginia (LPPM Universitas Jambi, 2026)
This study aims to analyze the influence of Brand Image, Perceived Value, and Brand Trust on the Repurchase Intention of Pinkflash products on the Shopee e-commerce platform. This research is motivated by the phenomenon of increasing e-commerce use for purchasing cosmetic products, as well as the issue of BPOM withdrawing the distribution permits for several Pinkflash products, which could potentially affect consumer perception and trust. The study uses a quantitative approach with data collected through questionnaires distributed to female consumers aged 17–30 who actively use Shopee and have previously repurchased Pinkflash products. The sample size in this study is 112 respondents, with a purposive sampling technique. The data analysis technique used is Structural Equation Modeling-Partial Least Square (SEM-PLS) with the help of SmartPLS application. The results show that Brand Image has a negative and significant effect. This shows that Pinkflash's image as a girly and trendy cosmetic product, with attractive packaging and affordable prices, hasn't fully been able to boost consumers' interest in repurchasing. Meanwhile, Perceived Value has a positive and significant effect on Repurchase Intention, which means the higher the perceived benefits, quality, comfort of use, and price appropriateness, the higher the tendency to repurchase. In addition, Brand Trust also has a positive and significant effect on Repurchase Intention, indicating that consumers' trust in Pinkflash's transparency, responsibility, and product safety can encourage them to repurchase.